2018
DOI: 10.1186/s12863-018-0608-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of lncRNA-controlled developmental gene expression during puberty in goat & rat

Abstract: BackgroundPuberty is a pivotal stage in female animal development, and marks the onset of reproductive capability. However, little is known about the function of lncRNAs (long noncoding RNAs) in puberty. Therefore, RNA-seq analysis were performed between goats and rats to clarify the roles of lncRNAs and mRNAs in the onset of puberty.ResultsIn the present study, the length of lncRNAs, the length of the open reading frame and the exon count were compared between the two species. Furthermore, functional annotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Increasingly numerous studies have opened the door to our understanding of noncoding small RNA molecules, however, lncRNA research is in its infancy, and the functions of most lncRNAs have not been determined. With the development of high-throughput sequencing technology, an increasing number of lncRNAs have been identified, and their functions have also become increasingly detailed [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly numerous studies have opened the door to our understanding of noncoding small RNA molecules, however, lncRNA research is in its infancy, and the functions of most lncRNAs have not been determined. With the development of high-throughput sequencing technology, an increasing number of lncRNAs have been identified, and their functions have also become increasingly detailed [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the GO functions and the genes involved are summarized in ( S5 Table ). In the identification and characterization of the late embryogenesis abundant proteins (LEA) in cotton, Magwanga et al [ 1 ], found that integral to membrane (GO: 0016021), was detected for over 95% of the LEA genes, and this he postulated to have a functional role in maintaining the cell membrane integrity. Moreover, in the analysis of the genes which could been introgressed into the backcross population, BC 2 F 2 developed from G .…”
Section: Resultsmentioning
confidence: 99%
“…The two parental lines flowers were tagged and samples harvested at 0, 5, 25 and 30 DPA for real time quantitative polymerase chain reaction (RT-qPCR). The RT-qPCR analysis was carried out as outlined by Magwanga et al [ 1 ], cotton GrActin with forward sequence “ ” and reverse sequence “ ” was used as the reference gene…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has investigated the role of lncRNA on growth development in muscles [41], heart [42], brain [43], spinal cord neuron [44] and cancer cells [45]. In addition, hypothalamic-pituitary-gonadal (HPG) axis plays an important role in reproduction, and there are many studies focus on hypothalamus [46,47], testis [48] and ovary [49] during different development stages. The pituitary gland is essential for mammalian reproduction and growth development owing to its function of GH, FSH, LH, and PRL hormone secretion.…”
Section: Discussionmentioning
confidence: 99%